Transportation costs, regional inequality and structural changes in the Brazilian economy: An interregional CGE approach - Eduardo Haddad; Geoffrey J.D. Hewings (European Regional Science Association (ERSA), 1998)
In this paper, an interregional computable general equilibrium model is used to evaluate the impacts of the changing macroeconomic environment of the Brazilian economy on the patterns of regional concentration and structural changes. The Brazilian Multisectoral and Regional/Interregional Analysis Model (B-MARIA) is the first fully operational interregional CGE model for Brazil. The model is based on the MONASH-MRF Model, which is the latest development in the ORANI suite of CGE models of the Australian economy. B-MARIA contains over 240,000 equations, and is currently used for policy analysis. Agents' behavior is modeled at the regional level, accommodating variations in the structure of regional economies. The model recognizes the economies of three Brazilian regions: North, Northeast and Center-South. Results are based on a bottom-up approach – national results are obtained from the aggregation of regional results. 40 sectors/commodities are identified in each region. Transportation services and the costs of moving products based on origin-destination pairs are explicitly modeled, taking into account the specific transportation structure cost of each commodity flow, which provides spatial price differentiation. The discussion of alternative strategies of regional development for the country shows that the open policies of the 1990's and the national strategies for increasing international competitiveness are very likely to increase regional imbalances in Brazil.
Keywords: 330